Sustaining home ownership in Australia: Emerging policy concerns - Wood, G.; Ong, Rachel (2012)
The idea that housing careers progress smoothly from leaving the parental home through renting and then ownership, with low housing costs cushioning lower post-retirement income, is losing its relevance in the 21st century. Secure housing careers in home ownership are being challenged by the risks associated with housing market volatility and innovation in mortgage markets as a result of financial deregulation. Increasing numbers of Australians are vulnerable to complex and insecure housing careers that feature tenure churning where a precarious foothold in home ownership is dislodged, commonly because of household dissolution, but sometimes because of other generally unanticipated adverse shocks. If growing numbers of Australians find home ownership unsustainable, it will add to the already intense pressure on housing assistance, especially among older Australians who are less likely to bounce back into home ownership given declining rates of economic participation in later years. This paper examines whether high levels of home ownership are sustainable in the early years of the 21st century and whether current Australian policy settings towards home ownership are optimal. We will draw on the published work of social researchers as well as our own empirical estimates to enrich understanding of the challenges faced by home ownership policy in Australia.